Peningkatan Hasil Belajar Ppkn Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Pada Siswa Kelas IX.1 SMP N 4 Pasaman - Sudirman S.Pd (STKIP Pesisir Selatan, 2016)
AbstractBased on the observations that have been done in SMPN 4 researchers concluded lace Pasaman pembelajaran results due to the lack of effective student learning model used by the teacher in the learning process. To the researchers as a classroom teacher conducts research on cooperative learning model jigsaw on learning outcomes. This research is a classroom action research. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 23 students. Data were collected by using observation sheet. Data were analyzed using percentages. Based on the analysis of research data that has been presented during two cycles and the results of the entire discussion, it can be concluded that cooperative learning model Jigsaw can improve the quality of teaching Civics and cooperative learning model Jigsaw has a positive impact in improving student learning outcomes characterized by increased mastery learning students in each cycle, the first cycle (68.18%), and the second cycle (90.91%).Keywords: Learning Outcomes PPKN, Cooperative Jigsaw mode